Active chiral control of GHz acoustic whispering-gallery modes - Mezil, Sylvain; Fujita, Kentaro; Osuka, Paul H.; Tomoda, Mononobu; Clark, Matt; Wright, Oliver B.; Matsuda, Osamu (American Institute of Physics, 2017)
We selectively generate chiral surface-acoustic whispering gallery modes in the gigahertz range on a microscopic disk by means of an ultrafast time-domain technique incorporating a spatial light modulator. Active chiral control is achieved by making use of an optical pump spatial profile in the form of a semicircular arc, positioned on the sample to break the symmetry of clockwise- and counterclockwise-propagating modes. Spatiotemporal Fourier transforms of the interferometrically monitored two-dimensional acoustic fields measured to micron resolution allow individual chiral modes and their azimuthal mode order, both positive and negative, to be distinguished. In particular, for modes with 15-fold rotational symmetry, we demonstrate ultrafast chiral control of surface acoustic waves in a micro-acoustic system with picosecond temporal resolution. Applications include nondestructive testing and surface acoustic wave devices.